2021
DOI: 10.1002/sstr.202000148
|View full text |Cite
|
Sign up to set email alerts
|

Liquid‐Based Exfoliation of Black Phosphorus into Phosphorene and Its Application for Energy Storage Devices

Abstract: Black phosphorus (BP) as a rising star among 2D materials has attracted attention for a wide range of applications due to its fascinating properties. The key point for the real application of phosphorene depends on its exfoliation technique to produce high‐quality nanosheets. In recent years, tremendous efforts have been made in the preparation and energy storage application of phosphorene and phosphorene‐based hybrid electrodes. Herein, the state‐of‐the‐art liquid‐based exfoliation and characterization of pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 207 publications
(250 reference statements)
0
25
0
Order By: Relevance
“…Electrochemical exfoliation (ECE) refers to current or voltage applied to a working electrode fixed to the bulk-layered crystal material, which drives counterions to the interlayer space, thereby reducing the vdWs force and finally achieving exfoliation of the corresponding 2D material. As a further method to prepare 2D materials in solvent, ECE possesses the advantages of being environmentally friendly, rapid, and convenient ( Rabiei Baboukani et al., 2021 ).…”
Section: Preparation Of Few-layer Bpmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical exfoliation (ECE) refers to current or voltage applied to a working electrode fixed to the bulk-layered crystal material, which drives counterions to the interlayer space, thereby reducing the vdWs force and finally achieving exfoliation of the corresponding 2D material. As a further method to prepare 2D materials in solvent, ECE possesses the advantages of being environmentally friendly, rapid, and convenient ( Rabiei Baboukani et al., 2021 ).…”
Section: Preparation Of Few-layer Bpmentioning
confidence: 99%
“…In 2014, the research teams of Ye (Liu et al, 2014) and Zhang (Li et al, 2014) independently reported that black phosphorus (BP), as a new elemental two-dimensional (2D) material, exhibits excellent electrical properties (mobility of $1000 cm 2 V À1 s À1 and on/off current ratio of up to 10 5 at room temperature) and anisotropic characteristics with a tunable bandgap (0.31 eV-1.0 eV), imparting BP with great potential for application in electronic and optoelectronic devices. The bandgap of 2D BP sits just between that of graphene (0 eV) (Novoselov et al, 2004) and transition-metal dichalcogenides (TMDs) (1.0 eV-2.0 eV) (Butler et al, 2013;Radisavljevic et al, 2011;Wang et al, 2012). Its photoresponse in the infrared (IR) range, together with its highly anisotropic light-mater interaction, makes BP an exciting new research topic in optoelectronics, photonics, and biomedicine based on 2D materials.…”
Section: Introductionmentioning
confidence: 99%
“…While the top-down techniques usually depend on mechanically or chemically weakening and wrecking the interlayer interactions between the bulk BP layers. [17] It includes mechanical exfoliation, ultrasonic exfoliation, laser irradiation, plasma thinning as well as electrochemical exfoliation. [18][19][20][21][22][23][24][25][26] The mechanical and ultrasonic exfoliation methods exhibit the disadvantage of low yield.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other 2-D materials, the production and large-scale exfoliation of phosphorene nanosheets should be anhydrous and free of oxygen because of the chemisorption of O-atoms by P-atoms present on the surface of BP nanosheets. 95–101…”
Section: Preparative Methodsmentioning
confidence: 99%